2014
DOI: 10.1063/1.4861061
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a generalized actuator disk wind turbine model into the weather research and forecasting model for large-eddy simulation applications

Abstract: A generalized actuator disk (GAD) wind turbine parameterization designed for large-eddy simulation (LES) applications was implemented into the Weather Research and Forecasting (WRF) model. WRF-LES with the GAD model enables numerical investigation of the effects of an operating wind turbine on and interactions with a broad range of atmospheric boundary layer phenomena. Numerical simulations using WRF-LES with the GAD model were compared with measurements obtained from the Turbine Wake and Inflow Characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
120
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(124 citation statements)
references
References 53 publications
3
120
1
Order By: Relevance
“…Moreover, after the evening transition, the hub-height wind-speed deficit persists for more than 15 km downwind, while the turbulence enhancement vanishes beyond 10 km downwind. In contrast to LES studies with constant atmospheric stratification (Churchfield et al 2012;Mirocha et al 2014Mirocha et al , 2015Abkar and Porté-Agel 2015;Vanderwende et al 2016a), the wake structure illustrated herein varies both temporally and spatially downwind of the wind farm. The turbine locations in these simulations, based on an actual wind farm, contribute to this variability.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Moreover, after the evening transition, the hub-height wind-speed deficit persists for more than 15 km downwind, while the turbulence enhancement vanishes beyond 10 km downwind. In contrast to LES studies with constant atmospheric stratification (Churchfield et al 2012;Mirocha et al 2014Mirocha et al , 2015Abkar and Porté-Agel 2015;Vanderwende et al 2016a), the wake structure illustrated herein varies both temporally and spatially downwind of the wind farm. The turbine locations in these simulations, based on an actual wind farm, contribute to this variability.…”
Section: Discussionmentioning
confidence: 50%
“…GAD model results have indicated that turbine wakes expand more in the horizontal direction than vertically (Mirocha et al 2014). At a downwind distance of 6.5 times the rotor diameter (D), the flow experiences up to 25% wind-speed reduction in a weakly convective regime (Mirocha et al 2014). LES has also revealed that the wind-speed deficit extends further downwind, the turbulence generation decreases and the overall wake recovers more slowly in the stable PBL than in the unstable PBL (Abkar and Porté-Agel 2015;Bhaganagar and Debnath 2015;Mirocha et al 2015).…”
Section: Turbine-wake Simulationsmentioning
confidence: 90%
See 2 more Smart Citations
“…This allows for better characterization of wake meandering and unsteady loads on turbines. Finally, wind plant modeling has also been improved through coupling to numerical weather prediction simulations (Fitch et al, 2012;Mirocha et al, 2014). Such simulations are able to incorporate synoptic-scale weather forcing and interactions between the surface, wind plant, and full atmospheric boundary layer.…”
Section: Wind Plant Flow Modelingmentioning
confidence: 99%